ACID-BASE BEHAVIOUR AND CU2+ AND ZN2+ COMPLEXATION PROPERTIES OF THE SEPIOLITE/WATER INTERFACE - Vico L.I. (My University, 2003)
Sepiolite is a clay mineral with a wide range of applications derived from its sorptive properties. In this work, aspects of the adsorption of Cu(II) and Zn(II) from aqueous solutions to particles of this material have been studied as a function of the pH and ionic strength of the medium. Cu2+, Zn2+, Mg2+ and Na+ in the suspensions were determined by atomic absorption spectrometry. Amounts of this cations interchanged had been calculated by the difference between concentrations before and after the contact with the mineral. The adsorption data suggest three possible mechanisms that could be involved in the interaction between metal ions like Cu2+ and the surface of the mineral: (1) A process of ion exchange in which Cu2+ replaces Na+. (2) Adsorption of Cu2+ on surface #SOH sites on the broken edges of the mineral with simultaneous release of protons. This mechanism takes into account the enhancement of adsorption with increasing pH. The final step of this reaction should be the incorporation of adsorbed cation to octahedral sheet. (3) Replacement of Mg2+ in the edges of octahedral sheet for Cu2+ could be another mechanism that contributes to the total adsorption phenomena. Similar mechanisms may involve the adsorption of Zn2+. The values obtained for complexation constants (constant capacitance model) were lower for this ion than for Cu2+.
Keywords: SEPIOLITE; ADSORPTION; COPPER; ZINC